Pengaruh kenaikan pangkat terhadap motivasi kerja Pegawai Negeri Sipil pada Dinas Pendidikan Kota Jambi - Hoirunnisah, Indah; Adriani, Zulfina; Wilian, Rohman (Jurnal Dinamika Manajemen, 2020)
The purpose of this study was to determine the description of promotion to the work motivation of civil servants and the effect of promotion on the work motivation of civil servants at the Jambi City Education Office. The sampling method uses a non-probability sampling method with an accidental sampling technique. The number of samples in this study amounted to 53 respondents obtained from the Slovin formula. The method of statistical analysis in this study consists of simple linear regression analysis, analysis of the coefficient of determination, and partial significance testing (t-test). The results of this study indicate that the promotion of civil servants of the Jambi City Education Office is in the category of many and work motivation is in the high category, then partially the promotion variable has a significant effect on the work motivation of the Civil Servants of the Jambi City Education Office. Therefore, the Jambi City Education Office must be able to maintain and try to continue to increase the promotion and work motivation.